Temperature and frequency dependent mean free paths of renormalized phonons in nonlinear lattices. (2nd February 2018) - Li, Nianbei; Liu, Junjie; Wu, Changqin; Li, Baowen
Abstract: Unraveling general properties of renormalized phonons are of fundamental relevance to the heat transport in the regime of strong nonlinearity. In this work, we directly study the temperature and frequency dependent mean free path (MFP) of renormalized phonons with the newly developed numerical tuning fork method. The typical 1D nonlinear lattices such as Fermi–Pasta–Ulam β lattice and ϕ 4 lattice are investigated in detail. Interestingly, it is found that the MFPs are inversely proportional to the frequencies of renormalized phonons rather than the square of phonon frequencies predicted by existing phonon scattering theory.